Unveiling Anemia Prevalence and Determinants in Urban and Rural Indian Populations: A Comprehensive Medical Study - Mohan Yadav (Scholars Digest Publishing, 2023)
Background: Although anemia is one of the leading causes of the global burden of disease, information about its prevalence in Indian is mostly missing. We therefore assessed its prevalence and associated factors in a Indian population.